2017
DOI: 10.1177/2057158517731719
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' motivation regulation and its relationship with engagement and burnout

Abstract: Motivation regulation, study engagement, and students' wellbeing are critical components of skillful self-regulated learning. However, few studies have focused on these factors and their relationship in nursing education and as there is an increased usage of blended learning in nursing education, measuring students' learning in this setting is increasingly important. This personoriented, quantitative study explored first-year nursing students' (N ¼ 90) motivation regulation related to study engagement and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…They were near the end of their studies: either about to graduate (n = 3) or graduating within 6 months (n = 9). Four students fit a permanent high-level MR profile, four fit a permanent less-developed MR profile, two were profile changers who shifted from a high-level to a less-developed MR profile, and two were profile F I G U R E 1 The phases of the analysis changers who shifted from a less-developed to a high-level MR profile (see Appendix 1; Mäenpää et al, 2018Mäenpää et al, , 2019.…”
Section: Resultsmentioning
confidence: 99%
“…They were near the end of their studies: either about to graduate (n = 3) or graduating within 6 months (n = 9). Four students fit a permanent high-level MR profile, four fit a permanent less-developed MR profile, two were profile changers who shifted from a high-level to a less-developed MR profile, and two were profile F I G U R E 1 The phases of the analysis changers who shifted from a less-developed to a high-level MR profile (see Appendix 1; Mäenpää et al, 2018Mäenpää et al, , 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Having a high level of motivation as the main effective factor, played a very important role in accelerating the development of students' clinical skills. Motivation has a pivotal role in orienting goals, learning strategies as well as self-regulation and, ultimately, educational achievement in students (Jannesar Hoseinie, Farmanbar, & Pourshaikhian, 2014;Mäenpää, Pyhältö, Järvenoja, & Peltonen, 2018;Rose, 2011). The ability to generate multiple ideas, or to have a flexible mindset, was one of the other individual attributes that helped students to achieve clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been suggested that motivations could play an important role in achieving educational goals, give learners energy, and consequently lead to the development of academic behaviors ( 13 14 ). In a study in Finland, it was revealed that higher levels of learning motivations of nursing students could be accompanied by higher academic engagement and lower academic burnout ( 14 ). It has been demonstrated that internal and external motivational factors can be the predictors of success in teaching nursing care.…”
Section: Discussionmentioning
confidence: 99%